Dry Stamping Coral Powder: An Effective Method for Isolating Coral Symbiotic Actinobacteria - Amayaly Becerril-Espinosa; Carolina Mateos-Salmón; Asdrubal Burgos; Fabián A. Rodríguez-Zaragoza; Iván D. Meza-Canales; Eduardo Juarez-Carrillo; Eduardo Rios-Jara; Héctor Ocampo-Alvarez (Microorganisms, 2023)
Actinobacteria are important sources of antibiotics and have been found repeatedly in coral core microbiomes, suggesting this bacterial group plays important functional roles tied to coral survival. However, to unravel coral–actinobacteria ecological interactions and discover new antibiotics, the complex challenges that arise when isolating symbiotic actinobacteria must be overcome. Moreover, by isolating unknown actinobacteria from corals, novel biotechnological applications may be discovered. In this study, we compared actinobacteria recovery from coral samples between two widely known methods for isolating actinobacteria: dry stamping and heat shock. We found that dry stamping was at least three times better than heat shock. The assembly of isolated strains by dry stamping was unique for each species and consistent across same-species samples, highlighting that dry stamping can be reliably used to characterize coral actinobacteria communities. By analyzing the genomes of the closest related type strains, we were able to identify several functions commonly found among symbiotic organisms, such as transport and quorum sensing. This study provides a detailed methodology for isolating coral actinobacteria for ecological and biotechnological purposes.